Analisis Penerapan Hatch and Carry Center sebagai Upaya Peningkatan Produktivitas dan Efesiensi Manajemen Buah Kelapa Sawit - Yusup Paisol; Gunawan, Sri; Astuti, Yohana Th. Maria; Afiantoro, Febri; Toni Athory Sinaga (Flora : Jurnal Kajian Ilmu Pertanian dan Perkebunan, 2025)
This study aims to analyze the effectiveness of the Hatch and Carry Center (H&C) in increasing the population of Elaeidobius kamerunicus pollinating weevils, fruit set levels, and Fresh Fruit Bunch (FFB) productivity in oil palm plantations at Division 6 Estate SGT 02, PT Kayung Agro Lestari, West Kalimantan. The research was conducted over six months, from July to December 2024, using a quasi-experimental comparative design. The period without H&C (July–December 2023) served as the control, while the period with H&C (July–December 2024) was treated as the intervention, allowing for a clearer analysis of differences before and after program implementation. Primary data were collected through monthly field observations on the number of male and female flowers, weevil populations, fruit set levels, and parthenocarpic fruits, providing consistent information on plant reproductive dynamics. In addition, in-depth interviews and Focus Group Discussions (FGDs) with stakeholders were conducted to identify supporting and inhibiting factors during implementation. Secondary data on FFB production were obtained from company harvest records in both periods to compare productivity trends. Quantitative data analysis employed the t-test to examine significant differences between the control and treatment periods, while qualitative data were thematically analyzed to explore the dynamics of program execution. The combination of both approaches is expected to provide a comprehensive understanding of the effectiveness of H&C as an innovation in oil palm pollination management.